Clinical efficacy and safety of acupuncture in the treatment for chronic spontaneous urticaria: a systematic review and meta-analysis - Wang Wei; Wang Wei; Yuxiang Wu; Shengyan Zhang; Bushuang Li; Zhengda Cheng; Wenjie Zhao; Wenjie Zhao (Frontiers in Medicine)
ObjectiveThis study aims to systematically evaluate the clinical efficacy and safety of acupuncture in treatment for chronic spontaneous urticaria (CSU) and provide evidence to inform clinical decision-making.MethodsA comprehensive search of eight Chinese and English databases was carried out. The search period spanned from the inception of the database up to 20 August 2024, and the search included randomized controlled trials (RCTs) on acupuncture for CSU, without language restrictions. Two independent researchers screened the resulting studies, evaluated their quality, and cross-checked their results. The extracted data were subjected to meta-analysis using RevMan 5.4 and Stata 15.ResultsA total of 22 RCTs involving 1,867 patients were included. Meta-analysis showed that acupuncture significantly improved the overall response rate, reduced the recurrence rate, decreased the urticaria activity score, and improved the Dermatology Life Quality Index, Hamilton Depression Scale, VAS itching score, and the Chronic Urticaria Quality of Life Questionnaire scores. Acupuncture also resulted in a reduced number and size of wheals, shortened duration of flare-ups, and reduced serum IgE, IFN-γ, and IL-4 levels. In addition, it led to significantly reduced traditional Chinese medicine syndrome scores, all with statistical significance. Furthermore, acupuncture did not significantly increase the incidence of adverse events, which indicates good safety. However, moderate to high bias and heterogeneity were observed in the included RCTs. Based on the Grading of Recommendations, Assessment, Development, and Evaluation evidence, this study provides a moderate to low recommendation for acupuncture in the treatment for CSU although the results remain promising.ConclusionAcupuncture appears to be an effective and safe treatment for CSU. However, further high-quality RCTs are needed to confirm its clinical efficacy and safety.